Synthesis, structure, and unprecedented solubility of lipophilic borate salts - Wrede, Michael; Frank, Viktoria; Kannenberg, Gerri; Rominger, Frank; Straub, Bernd Franz (Inorganica chimica acta, 2011)
The multi-gram scale preparation of halide free lipophilic borate salts from inexpensive precursor compounds 3,3′,5,5′-tetra-tert-butyl-2,2′-biphenol and tetrahydridoboranate salts is reported. The so-called “bortebate” anion is more stable against water and bases than its aluminum analog “altebate”, but bortebate formation is significantly slower. Bortebate salts are highly soluble in hydrocarbon solvents, e.g. >35mmol/L lithium bortebate in pentane at 20°C. Quantitative salt metathesis reactions between sodium bortebate and halide salts can be easily achieved by precipitation of the sodium halide in methylene chloride.
Available online 28 December 2010
Gesehen am 05.12.2022